Pengembangan Sistem Informasi Terintegrasi Pendaftaran Ekstrakurikuler Berbasis Web Mobile pada SMA Negeri 1 Gedong Tataan - Wahyu Sulistianing Budi; Tria Peronika; Tuti Puspitasari (YHMM PUBLISHING, 2025)
This study aims to design and implement a web-mobile-based extracurricular registration information system to improve the effectiveness and efficiency of extracurricular management at SMA Negeri 1 Gedong Tataan. The system addresses problems arising from manual registration processes, such as data inconsistency, limited information accessibility, and inefficiencies in managing student participation. The system was developed using a structured system development approach, combining the Waterfall and System Development Life Cycle (SDLC) methods, supported by Unified Modeling Language (UML) for system modeling and a prototype approach for user interface design. The application provides integrated features including online registration, user account management, extracurricular scheduling, attendance tracking, assessment management, and centralized reporting. The implementation results indicate that the system enhances data accuracy, reduces administrative workload, improves information transparency, and increases accessibility through mobile devices. Overall, the proposed system contributes to improved extracurricular management performance and supports the digital transformation of school administrative services.